Implications of survey methods on travel and non-travel activities: A comparison of the Austrian national travel survey and an innovative mobility-activity-expenditure diary (MAED) - Aschauer, Florian; Hössinger, Reinhard; Axhausen, Kay W.; Schmid, Basil; Gerike, Regine (European Journal of Transport and Infrastructure Research, 2018)
This paper contributes to the research on non-reporting effects in mixed-method household travel surveys (HTS) in two ways: Firstly, we compare travel activities reported in the established Austrian National HTS (ANTS) with an innovative survey approach, the so-called “MobilityActivity-Expenditure Diary” (MAED), and secondly we extend the analysis to (i) additional travel estimates and to (ii) non-travel activities. The analysis addresses three main goals: (i) identification of non-reporting effects in the HTS for travel estimates, (ii) analysis of speed-ofresponse effects on travel estimates, (iii) assessment of the completeness and accuracy of nontravel activities inferred from the trip purposes in the HTS. Underreporting in HTS occurs both on person level and on the trip level, and mainly for peak-hour trips with either short distances or short durations of the subsequent non-travel activity. No significant underreporting was found on the tour level. Speed-of-response effects are small in both surveys but significant for the ANTS. The duration of non-travel activities per activity type corresponds well in the MAEDsurvey and in the ANTS but the information in the MAED-survey is much richer. The results can be used threefold: (i) to develop correction factors that account for systematic biases in HTS, (ii) to identify omitted items (trip frequency, duration, distance etc.) if HTS data are used without correction factors, and (iii) to demonstrate the importance of high quality field work and validation.